Analysis of Different Approaches for the Selection of Reference Genes in RT-qPCR Experiments: A Case Study in Skeletal Muscle of Growing Mice - Piazza, Verónica G. (Int J Mol Sci, 2017)
The reliability of reverse transcription-quantitative PCR (RT-qPCR) results in gene expression studies depends on the approaches used to account for non-biological variations. In order to find a proper normalization strategy for the study of genes related to growth hormone signaling in skeletal muscle of growing mice, nine unrelated genes were evaluated as internal controls. According to the most used algorithms–geNorm, the Comparative ΔCq method, NormFinder and BestKeeper–GSK3B, YWHAZ, RPL13A and RN18S were found as the most stable. However, the relative expression levels of eight of the potential reference genes assessed decreased with age in cDNA samples obtained from the same amount of total RNA. In a different approach to analyze this apparent discrepancy, experiments were performed with cDNA obtained from equal amounts of purified mRNA. Since the decline was still observed, the hypothesis of an age-related change in mRNA to total RNA ratio that could account for the systematic decrease was rejected. Differences among experimental groups could be due to a substantial increase with age in highly expressed mRNAs, which would bias the quantitation of the remaining genes. Consequently, those reference genes reflecting this dilution effect, which would have been discarded considering their variable relative expression levels, arose as suitable internal controls.